2020
DOI: 10.1155/2020/8653783
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhizin Ameliorates Radiation Enteritis in Mice Accompanied by the Regulation of the HMGB1/TLR4 Pathway

Abstract: Radiation enteritis is a common side effect of radiotherapy for abdominal and pelvic malignancies, which can lead to a decrease in patients’ tolerance to radiotherapy and the quality of life. It has been demonstrated that glycyrrhizin (GL) possesses significant anti-inflammatory activity. However, little is known about its anti-inflammatory effect in radiation enteritis. In the present study, we aimed to investigate the potential anti-inflammatory effects of GL on radiation enteritis and elucidate the possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…In contrast to PAMPs, endogeneous molecules which incur immune response are defined as alarmin (or damage associated molecular patterns, DAMPs) and HMGB1 is an example of this category 24 , 25 . Radiation is one stimuli that cause tissue damage without pathogens 24 , and extracellular HMGB1 has been found to increase after irradiation 22 , 23 . In this study, we demonstrated that both mRNA expression and serum levels of HMGB1 and pro-inflammatory cytokines such as TNF-α, IL-6, IL-1α and IL-1β increase dose dependently after 0.1 Gy and 1 Gy radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to PAMPs, endogeneous molecules which incur immune response are defined as alarmin (or damage associated molecular patterns, DAMPs) and HMGB1 is an example of this category 24 , 25 . Radiation is one stimuli that cause tissue damage without pathogens 24 , and extracellular HMGB1 has been found to increase after irradiation 22 , 23 . In this study, we demonstrated that both mRNA expression and serum levels of HMGB1 and pro-inflammatory cytokines such as TNF-α, IL-6, IL-1α and IL-1β increase dose dependently after 0.1 Gy and 1 Gy radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, GL can ameliorate ischemic-reperfusion injury, hepatotoxicity, and acute kidney injury by inhibiting the HMGB1 pathway 20 , 21 . It can also mitigate radiation-induced tissue injuries such as radiation-induced acute lung injury 22 or radiation enteritis 23 . However, past studies have only looked into HMGB1 and the abovementioned protective effects of GL after relatively high doses of radiation (20 Gy and 6.5 Gy, respectively) 22 , 23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For IHC analysis, paraffin-embedded mouse colon sections were deparaffinized in xylene and hydrated in a series of alcohols. After heat-induced antigen retrieval and blocking with 1% skim milk, the sections were incubated overnight with primary antibodies (8-NitroG (Pinlaor et al, 2004 [ 31 ], 1:400)); 8-OxodG (JaICA, MOG-100p, 1:400); HMGB1 (Abcam, 18256, 1:400); COX2 (Santa Cruz Biotechnology, Inc., SC-1745, 1:400); YAP1 (Abcam, ab 39361, 1:400); SOX9 (Abcam, ab 185230, 1:400)), and then incubated with an avidin–biotin complex (Vectastain ABC kit, Vector Laboratories Burlingame, CA, USA). The immunoreaction was visualized using a peroxidase DAB kit (Nacalai Tesque Inc., Kyoto, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Although some researchers have studied the effect of GL on colitis [ 30 , 31 , 32 ], the effect of GL on ulcerative colitis colorectal cancer caused by an azoxymethane (AOM)/dextran sodium sulfate (DSS) model is not known. Therefore, we investigated whether GL can suppress inflammation and carcinogenesis, using a carcinogen (AOM)/colorectal inflammatory agent (DSS)-induced murine model of colorectal cancer, and assessed the molecular mechanisms involved.…”
Section: Introductionmentioning
confidence: 99%